Electrically Tunable Momentum Space Polarization Singularities in Liquid Crystal Microcavities - Przemysław Oliwa; Piotr Kapuściński; Maria Popławska; Marcin Muszyński; Mateusz Król; Przemysław Morawiak; Rafał Mazur; Wiktor Piecek; Przemysław Kula; Witold Bardyszewski; Barbara Piętka; Helgi Sigurðsson; et al. (Advanced Science)
Abstract Momentum space polarization singularities of light appear as vectorial twists in the scattered and radiated far field patterns of exotic photonic structures. They relate to important concepts such as bound states in the continuum, spatiotemporal light steering, polarization Möbius strips, Berry curvature, and associated topological photonic phenomena. Polarization singularities, such as completely circularly polarized C‐points, are readily designed in real space through interference of differently polarized beams. In momentum space, they require instead sophisticated patterning of photonic crystal slabs of reduced symmetries in order to appear in the corresponding band structure with scarce in situ tunability. Here, it is shown that momentum space singularities can be generated and, importantly, electrically tuned in the band structure of a highly birefringent planar liquid crystal microcavity that retains many symmetries. The results agree with theoretical predictions and offer exciting possibilities for integration of momentum space polarization singularities in spinoptronic technologies.